Question Student Have Method: Upaya Meningkatkan Motivasi dan Prestasi Belajar PPKn Menggunakan Media Kartu “Ji-Tu” di MTs Negeri 9 Sleman - Hartoyo Mugiraharjo (Jurnal Pendidikan Madrasah, 2022)
This research aims to increase the motivation and achievements of learning Pancasila Education and Citizenship Class VIII-C MTs Negeri 9 Sleman, School Year 2020-2021. This research is Classroom Action Research conducted collaboratively. The subject of this study is class VIII-C MTs Negeri 9 Sleman which amounted to 30 students. The objects in this study increased motivation and learning achievement. Data collection techniques in this study were carried out with observation techniques, tests, and questionnaires. Data analysis methods with quantitative descripttic techniques. The results showed that learning motivation in cycle I by 66.66% and cycle II by 86.66, increased by 26%. Learning achievement increased in silus I by 65.00 and in cycle II to 77.11. Question Student Have method by utilizing the media card "Ji-Tu" can be applied to students in Madrasah Tsanawiyah.